Combining Rigid Cellulose Nanocrystals and Soft Silk Proteins: Revealing Interactions and Alignment in Shear - Ilona Leppänen; Suvi Arola; Alistair W. T. King; Miriam Unger; Hartmut Stadler; Gry Sofie Nissen; Charlotte Zborowski; Tommi Virtanen; Juha Salmela; Harri Setälä; Stephanie Lésage; Monika Österberg; et al. (Advanced Materials Interfaces, 2023)
Abstract Natural materials, such as silk and cellulose, have an inspiring set of properties, which have evolved over hundreds of millions of years. In this study, cellulose nanocrystals (CNCs) and regenerated silk fibroin (RSF) are combined to evaluate their suitability for filament formation. This is assessed by tuning and characterizing the interactions between these two materials and finally by studying the alignment of the mixtures under shear. To modify the interactions between CNCs and silk, CNCs with varying surface functionalities (sulfate and/or aminosilane groups) are used. The interactions and compatibility of the two components are investigated using quartz crystal microbalance with dissipation monitoring (QCM‐D) and photothermal atomic force microscopy (AFM‐IR), which show that ionic interactions induce sufficient binding between the two components. Then, the alignment of the CNC and silk mixtures is evaluated by shear‐induced polarized light imaging, which indicates that silk can orientate with the CNCs when not covalently bound. Finally, the potential of the materials for filament formation is tentatively demonstrated using an industrial dry‐spinning environment, where CNCs are expected to bring order and alignment, whereas RSF provides soft and more mobile regions to further facilitate the alignment of the final filament structure.